Managing Islamic Education to Overcome Juvenile Delinquency - Rapi, M. (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
Reconstructing patterns of Islamic education to be basic values of religion provides the scope of Islamic education development. Education is an effort to preserve, transfer and transform cultural good values in all its aspects to the younger generation. Patterns of Islamic education in tackling juvenile delinquency including efforts to improve Muslim education strategies concerning the issue of how the implementation of the educational goals of the educational process by looking at the situation and condition, and also how to keep the process there are no disturbances, internally and externally, regarding institutional or social environments. The application of preventive methods (prevention), curative (treatment) and rehabilitative (quarantine) are pivotal for an educator or school organizers, to coach young people in schools can be focused well; therefore, at least it is to reduce misbehavior frequency among adolescents.—–Rekonstruksi pola pendidikan Islam merupakan suatu keharusan dalamÂ menempatkan nilai-nilai dasar agama yang menyediakan lingkup pengembangan pendidikan Islam. Pendidikan adalah upaya untuk melestarikan, mentransfer dan mengubah nilai-nilai budaya dalam segala aspeknya yang baik untuk generasi muda. Pola pendidikan Islam dalam menanggulangi kenakalan remaja termasuk upaya untuk meningkatkan strategi pendidikan Islam mengenai masalah bagaimana pelaksanaan tujuan pendidikan dari proses pendidikan dengan melihat situasi dan kondisi, serta bagaimana untuk menjaga proses tersebut supaya berjalan tanpa hambatan, internal dan eksternal, dalam lingkungan kelembagaan atau sosial. Penerapan metode preventif (pencegahan), kuratif (pengobatan) dan rehabilitatif (karantina) sangat diperlukan untuk seorang pendidik atau sekolah penyelenggara untuk pembinaan generasi muda di sekolah-sekolah dapat difokuskan baik sehingga setidaknya mengurangi frekuensi perilaku negatif yang terjadi pada remaja.